Host Biology and Anthropogenic Factors Affect Hepadnavirus Infection in a Neotropical Bat - Hiller, Thomas; Rasche, Andrea; Brändel, Stefan Dominik; König, Alexander; Jeworowski, Lara; O'Mara, M. Teague; Cottontail, Veronika; Page, Rachel A.; Glebe, Dieter; Drexler, Jan Felix; Tschapka, Marco (My University, 2019)
The tent-making bat hepatitis B virus (TBHBV) is a hepadnavirus closely related to human hepatitis B virus. The ecology of TBHBV is unclear. We show that it is widespread and highly diversified in Peters’ tent-making bats (Uroderma bilobatum) within Panama, while local prevalence varied significantly between sample sites, ranging from 0 to 14.3%. Females showed significantly higher prevalence than males, and pregnant females were more often acutely infected than non-reproductive ones. The distribution of TBHBV in bats was significantly affected by forest cover, with higher infection rates in areas with lower forest cover. Our data indicate that loss of natural habitat may lead to positive feedback on the biotic factors driving infection possibility. These results underline the necessity of multidisciplinary studies for a better understanding of mechanisms in pathogen–host relationships and for predictions in disease ecology.
Keywords: Uroderma bilobatum, Bat, Habitat loss, TBHBV, Hepatitis B virus, Orthohepadnavirus; 570